Clinical and functional outcomes after augmented hip abductor tendon repair. Issue 1 (January 2018) - Ebert, Jay R.; Bucher, Thomas A.; Mullan, Conor J.; Janes, Gregory C.
Introduction: Hip abductor tendon (HAT) tearing is commonly implicated in greater trochanteric pain syndrome. Surgical studies are often reported in small cohorts and with limited information on functional improvement. This study reports the clinical and functional outcomes after HAT repair. Methods: 112 patients with symptomatic HAT tears, diagnosed via magnetic resonance imaging, underwent open bursectomy, V-Y lengthening of the iliotibial band, debridement of the diseased tendon, decortication of the trochanteric foot-plate and reattachment of the tendon with suture anchors, augmented with a LARS ligament through a trans-osseous tunnel. Patients were evaluated pre-surgery and at 3, 6 and 12 months post-surgery using the Harris (HHS) and Oxford (OHS) Hip Scores, SF-12, hip range of motion, 6-minute walk and 30-second single leg stance tests. Maximal isometric hip abduction strength (HAS) was assessed and limb symmetry indices (LSIs) were calculated between the operated and non-operated limbs. Patient satisfaction and perceived global rating of change (GRC) was evaluated. Analysis of variance evaluated improvement over time. Results: There was a significant improvement (p<0.05) in all clinical and functional measures. HAS significantly improved over time (p<0.002) and all LSIs were >85% at 12 months. At 12 months, a mean GRC score of 3.5 (range -1 to 5) was reported, while 96% of patients were satisfied with their surgical outcome. There was a 2.7% (n = 3) failure rate at 12 months. Conclusions: HAT reconstruction, augmented with a synthetic ligament, demonstrated significantly improved clinical and functional outcomes, high levels of patient satisfaction and a low failure rate to 12 months post-surgery.